Populist polarization and the slow death of democracy in Ecuador. Issue 2 (23rd February 2016) - de la Torre, Carlos; Ortiz Lemos, Andrés
Abstract : This article analyses how the interactions between a strong populist government in Ecuador and a weak, divided, and inefficient internal opposition in a context of weak liberal institutions could lead to what Guillermo O'Donnell termed "the slow death of democracy". Rafael Correa was elected with a substantive project of democratization understood as economic redistribution and social justice. His administration got rid of neoliberal policies and decaying traditional political parties, while simultaneously co-opting social movements, regulating civil society, and colonizing the public sphere. Because the judiciary was subordinated to Correa, social movement activists, journalists, and media owners could not use the legal system to resist Correa's crack down of civil society and regulation of the privately owned media. They took their grievances to supranational organizations like the Organization of American States. When these organizations stepped in to challenge Correa, his government denounced imperialist intervention in his nation's internal affairs, and advocated for the creation of new supranational institutions without US presence.